Transcutaneous spinal DC stimulation reduces pain sensitivity in humans. (4th March 2015) - Meyer-Frießem, C.H.; Haag, L.M.; Schmidt-Wilcke, T.; Magerl, W.; Pogatzki-Zahn, E.M.; Tegenthoff, M.; Zahn, P.K.
Highlights: Anodal tsDCS reduces pain sensitivity to painful mechanical pinprick stimuli. This is the first evidence that tsDCS sensory effects last longer than 30min. Anodal tsDCS had no effect on pain sensitivity to single electrical pulses. Abstract: Non-invasive approaches to pain management are needed to manage patient pain escalation and to providing sufficient pain relief. Here, we evaluate the potential of transcutaneous spinal direct current stimulation (tsDCS) to modulate pain sensitivity to electrical stimuli and mechanical pinpricks in 24 healthy subjects in a sham-controlled, single-blind study. Pain ratings to mechanical pinpricks and electrical stimuli were recorded prior to and at three time points (0, 30, and 60 min) following 15 min of anodal tsDCS (2.5 mA, "active" electrode centered over the T11 spinous process, return electrode on the left posterior shoulder). Pain ratings to the pinpricks of the highest forces tested (128, 256, 512 mN) were reduced at 30 min and 60 min following anodal tsDCS. These findings demonstrate that pain sensitivity in healthy subjects can be suppressed by anodal tsDCS and suggest that tsDCS may provide a non-invasive tool to manage mechanically-induced pain.